Development of E-Learning Module: Historical Culture Society Based on Local Genius - Aprianto, Diky; Umamah, Nurul; Sumardi, Sumardi (JURNAL HISTORICA, 2017)
A module has the characteristics required by the curriculum of 2013. It is the teaching materials that emphasize student-centered learning paradigm. Curriculum 2013, is a curriculum that aims to build the national character of learners. One of its implementation, which is implementing learning that relates to the needs of the environment around the learner. Thus, they invented the electronic module in the history of Using culture society (local history) as an effort to fulfil the demands of learning in the Curriculum 2013. The purpose of this study was to develop an electronic module validated experts and effectively used as a learning material about the history of Using culture society in tenth-grade high school student in Banyuwangi. This study uses research method of development with Borg & Gall model. Data collection research using techniques of documentation, observation, questionnaires, interviews, and tests. Subjects of this study involving five teachers of historical subjects and 158 tenth grade students from five high school in Banyuwangi. The results of research and development of electronic modules in the history of Using society shows, validation material experts scored 76% were categorized "good", the validation linguists scored 100% were categorized "excellent", validation expert instructional design scored 82% were categorized "good ", and test users scored 84.66% were categorized "good ". Then, the small group trial scored 62.87% were categorized "moderate effectiveness". Test the effectiveness of an electronic module in the history of Using society in field trials scored 71.57% were categorized "high effectiveness ". Based on the results of the study, the electronic modules in the history of Using society appropriate and effective used as learning material of tenth-grade high school student subjects of Indonesian history in Banyuwangi. It is expected, researchers can then develop similar modules in accordance with the demands of the implementation of Curriculum 2013. Thus, the students as the next generation are not uprooted their cultural roots and maintain its existence. Keywords: E-Learning Module, cultural history, Using Society